Menemukan Kansha di Tengah Perayaan Hidup: Kajian Semiotika terhadap Lirik Lagu “Matsuri” karya Fujii Kaze - Gratcia Agustina; Irwan; Nabiilah Putri Tarigan (Ayumi : Jurnal Budaya, Bahasa dan Sastra, 2026)
This study aims to describe and analyze the representation of the value of Kansha (gratitude) in the lyrics of the song “Matsuri” by Fujii Kaze. As a product of popular culture, this song is noteworthy for its philosophical depth, which reconstructs the meaning of traditional Japanese festivals within a modern spiritual context. This study employs a descriptive qualitative approach based on Michael Riffaterre's theory of Semiotics. The research data consists of lingual units in the lyrics of “Matsuri,” analyzed through heuristic and hermeneutic reading stages, identification of indirect expression, and the search for matrices and hypo grams. The results indicate that the value of Kansha in this song is interpreted not merely as a conventional expression of thanks, but as an "existential gratitude." The findings identify three main pillars of Kansha: (1) gratitude as a form of total acceptance of the life cycle (birth and death), (2) gratitude as an awareness of self-sufficiency「知足」(chisoku) that rejects social comparison, and (3) gratitude as a manifestation of spiritual resilience「有り難し」 (arigatashi) in the face of suffering. The song successfully transforms the concept of matsuri from a communal physical ritual into a continuous internal ritual of gratitude.